2016
DOI: 10.1007/s12192-015-0639-3
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy as a defense strategy against stress: focus on Paracentrotus lividus sea urchin embryos exposed to cadmium

Abstract: Autophagy is used by organisms as a defense strategy to face environmental stress. This mechanism has been described as one of the most important intracellular pathways responsible for the degradation and recycling of proteins and organelles. It can act as a cell survival mechanism if the cellular damage is not too extensive or as a cell death mechanism if the damage/stress is irreversible; in the latter case, it can operate as an independent pathway or together with the apoptotic one. In this review, we discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 65 publications
1
33
0
Order By: Relevance
“…However, Kobayashi et al (50) reported that suppression of autophagy exerted protective effects against HG-mediated cardiomyocyte injury. In the present study, the results also indicated that the HG group displayed increased apoptosis compared with the NG group, and promotion of autophagy promotes apoptosis, which is a stress phenomenon (51).…”
Section: Discussionsupporting
confidence: 68%
“…However, Kobayashi et al (50) reported that suppression of autophagy exerted protective effects against HG-mediated cardiomyocyte injury. In the present study, the results also indicated that the HG group displayed increased apoptosis compared with the NG group, and promotion of autophagy promotes apoptosis, which is a stress phenomenon (51).…”
Section: Discussionsupporting
confidence: 68%
“…In fact, these two processes are more often than not mutually exclusive [10][11][12], and often activation of one pathway over another can mean the difference between an adaptive or death response [12,78,88]. Our results demonstrated a clear activation of apoptosis over autophagy in our susceptible coral species, probably triggered by excessive immune stress [12,78]. The induction of apoptosis over autophagy is possibly a result of the inability of susceptible corals to respond to the stressor and/or limited plasticity in their response.…”
Section: (B) Autophagy Is Key In Disease-tolerant Coral Speciesmentioning
confidence: 61%
“…Corals that recover post-temperature stress and bleaching are characterized by inhibition of apoptotic pathways, while those that experience mortality following these events are marked by increased apoptotic activity [77]. In other invertebrates, apoptosis is the last resort under stressful conditions, and if stress continues, death results due to excessive cell death [78].…”
Section: (A) Apoptosis Is Activated In Disease-susceptible Speciesmentioning
confidence: 99%
“…Autophagy contributes to maintenance of cellular homeostasis. It regulates elimination and recycling of damaged intracellular compartments, also providing energy (ATP) for the apoptotic machinery [ 52 ]. Thus, human cells and embryos can tolerate chemical injury (e.g., heptadienal), trying to reduce its harmful effects and damages.…”
Section: Discussionmentioning
confidence: 99%